2021
DOI: 10.3390/s21062219
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Customized 360-Degree Experiences for Stress Relief

Abstract: The latest studies in virtual reality (VR) have evidenced the potential of this technology to reproduce environments from multiple domains in an immersive way. For instance, in stress relief research, VR has been presented as a portable and inexpensive alternative to chromotherapy rooms, which require an adapted space and are expensive. In this work, we propose a portable and versatile alternative to the traditional chromotherapy color-loop treatment through four different 360-degree virtual experiences. A gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 69 publications
0
11
0
1
Order By: Relevance
“…Here, gamma power is compared to the combined power in the theta and alpha frequency bands. Results from the reactive phase report higher relative gamma values compared to a control condition and a decrease during the recovery phase compared to the reactive phase ( Minguillon et al, 2016 , 2017 ; Vaquero-Blasco et al, 2020 , 2021 ). These results seem mostly driven by changes in the theta and alpha band rather than the gamma band, and high variability exists between participants, showing that psychosocial stress exposure leads to different neurological adjustments between people.…”
Section: Discussionmentioning
confidence: 79%
“…Here, gamma power is compared to the combined power in the theta and alpha frequency bands. Results from the reactive phase report higher relative gamma values compared to a control condition and a decrease during the recovery phase compared to the reactive phase ( Minguillon et al, 2016 , 2017 ; Vaquero-Blasco et al, 2020 , 2021 ). These results seem mostly driven by changes in the theta and alpha band rather than the gamma band, and high variability exists between participants, showing that psychosocial stress exposure leads to different neurological adjustments between people.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, other psychophysiological parameters with higher temporal resolution might have shown differences between the recovery conditions, such as HRV (Anderson et al 2017;Liszio et al 2018), or electroencephalography (EEG; Bilgin et al 2019;Vaquero-Blasco et al 2021). In contrast to HR (beats per minute), HRV measures specific changes in time (or variability) between the R-R intervals in milliseconds (Malik et al 1996).…”
Section: Limitations and Alternative Explanationsmentioning
confidence: 99%
“…Therefore, future studies should explore EEG activity during exposure to a virtual natural environment. Recent research demonstrated that EEG can be used to quantify physical relaxation responses during a monoscopic 360°nature video presented via 6DoF HMD (Vaquero-Blasco et al 2021). Moreover, the authors argued that EEG is less susceptible to artifacts compared to SCL and HR measures and benefits from high temporal resolution.…”
Section: Limitations and Alternative Explanationsmentioning
confidence: 99%
“…Neste contexto, estudos clínicos demonstram a eficácia da TERV no cuidado em saúde. Sua utilização vem sendo direcionada a doenças, condições e sintomatologias, como tratamento da dor (aguda e crônica), para sua atenuação e/ou distração frente a terapias invasivas (Ahmadpour et al, 2019), fadiga (Ioannou et al, 2020), distúrbios do sono (Lee & Kang, 2020), controle do estresse (Vaquero-Blasco et al, 2021), fobias, ansiedade e depressão (Felnhofer et al, 2019), reabilitação motora (Tieri et al, 2018), entre outros. Além disso, a TERV pode facilitar a compreensão e aceitação da doença por parte do paciente e seus familiares, bem como o trabalho de aspectos motivacionais para início e manutenção do tratamento (Hsieh, 2020), afirmação da vida e aceitação da morte como processo natural, além de estímulos à interação social, afetividade e espiritualidade (Murdoch & Davies, 2017;Wijma et al, 2018).…”
Section: Introductionunclassified